Using intra-brain drug infusion to investigate neural mechanisms underlying reward-seeking behavior in mice - Chang Xu; Beibei Peng; Shuai Liu (STAR Protocols, 2022)
Summary: Brain-region-specific drug infusion is a key way to investigate neural mechanisms underlying behavior and neurological diseases. Here, we present a detailed protocol for cannula implantation, intra-brain drug infusion, and two reward-seeking-related behavioral paradigms in mice: the light/dark box test and touchscreen version of progressive ratio test. In addition, we provide a user-friendly Python-based tool for behavioral data analysis. This protocol can be easily adapted to address various research questions related to behavioral pharmacology.For complete details on the use and execution of this protocol, please refer to Peng et al. (2021).